Characterization and Assessment of Flavor Compounds and Some Allergens in Three Iranian Rice Cultivars during Gelatinization Process by HS-SPME/GC-MS - M. H. Givianrad (E-Journal of Chemistry)
A combined gas chromatography mass spectrometry with headspace solid-phase microextraction method has been utilized for the analysis of the flavor volatiles of three different rice cultivars including two modified Iranian rice cultivars and Hashemi rice cultivar during gelatinization. As a result, while gelatinization would progress, the amount of the volatile compounds would be also increased. Altogether, 74, 55 and 66 components were identified for Hashemi, HD5 and HD6 rice samples, respectively, which 56 unique compounds were not identified, previously. Subsequently, seven fragrance chemicals have been detected, which were most frequently reported as contact allergens in the European Union.